The Indonesian health legal system provides legal protection for pharmacists in pharmaceutical practice - Shaumy, Rindwita Vania; Tri Umiana Soleha; Citra Yuliyanda Pardilawati (Nursing and Health Sciences Journal (NHSJ), 2025)
Implementing Law No. 17 of 2023 on health has significantly changed the Indonesian health legal system, including legal protection for pharmacists. The enactment of Health Law No. 17/2023 represents a pivotal advancement in Indonesia’s health legal framework, particularly in addressing gaps in legal protection for pharmacists amid evolving healthcare practices. This study aims to analyze the impact of these regulations on the legal protection of pharmacists in pharmaceutical practice, both conventionally and electronically. The method used is a literature review of various legal sources, scientific literature, and relevant laws and regulations. It is assisted by the Publish or Perish (PoP) application for qualitative analysis. The results of the discussion show that although this law has provided a clearer legal basis for the practice of pharmacists, such as authority in services, the right to stop services under certain conditions, and regulation of the distribution of hard drugs, there are still shortcomings in implementation and strict legal sanctions. Pharmaceutical cases still occur frequently, including in electronic services and misuse of hard drugs, indicating that the existing legal protection has not been entirely adequate. While Law No. 17/2023 provides a foundational legal framework, its impact is constrained by ambiguities in operational protocols and lenient sanctions. This study concludes that Law No. 17 of 2023 is a positive first step in strengthening the legal position of pharmacists but needs to be accompanied by further technical regulations and consistent law enforcement so that legal protection can be maximized.